Product efficiency in the Spanish automobile market - Eduardo González; Juan Ventura; Ana Cárcaba (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
This paper evaluates product efficiency in the Spanish automobile market. We use non parametric frontier techniques in order to estimate product efficiency scores for each model. These scores reflect the minimum price for which each car could be sold, given the bundle of tangible features it offers in comparison to the best-buy models. Unlike previous research, we use discounted prices which have been adjusted by car dealerships to meet sale targets. Therefore, we interpret the efficiency scores as indicators of the value of the intangible features of the brand. The results show that Audi, Volvo, Volkswagen and Mercedes offer the greatest intangible value, since they are heavily overpriced in terms of price/product ratios. Conversely, Seat, Kia, Renault and Dacia are the brands that can be taken as referent in terms of price/product ratios.
Keywords: C61; D13; D61; L62; L81; 330; Product efficiency; DEA; Automobile; Spain